The effect of think-pair-share-write based on hybrid learning on metacognitive skills, creative thinking and cognitive learning at SMA negeri 3 Malang - Siregar, Ika Yulianti; Susilo, Herawati; Suwono, Hadi (University of Muhammadiyah Malang, 2017)
The results of biology learning observation show that there are many constraints during the learning process in the class and consultation meeting between teacher and students. The think-pair-share-write based on hybrid learning was conducted to analyze the effect on metacognitive skills, creative thinking and learning outcomes. The research design was quasi experiment with pretest-posttest non-equivalent control group design. The independent variable is think-pair-share-write based on Hybrid learning model, while the dependent variables are metacognitive skills, creative thinking, and cognitive learning outcomes. Metacognitive skills are measured by using metacognitive rubrics. Creative thinking skills and cognitive learning outcomes are measured by using a description test. The data were taken by conducting pretest and posttest. The hypothesis test used was anakova with level of significance 0,05 (P <0,05), as the test result was significant then the test was continued to LSD. Before the anakova test, normality and homogeneity test were performed. The results showed that think-pair-share-write based on Hybrid Learning significantly affecting: 1) the metacognitive skills with F arithmetic of 183,472 and Sig. 0,000; 2) the creative thinking skill with F value of 325,111 and Sig. 0,000; 3) the cognitive learning outcomes with F arithmetic of 175.068 and Sig. 0,000.